2002
DOI: 10.1001/archneur.59.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Idiopathic Axonal Polyneuropathy and Successful Aging of the Peripheral Nervous System in Elderly People

Abstract: Neither aging of the peripheral nervous system nor disease duration affects CIAP to a considerable degree, but CIAP has a greater influence on the daily life of nonretired patients with early-onset CIAP. The diagnosis of axonal polyneuropathy is probably supported best by either the absence of the sural nerve sensory nerve action potentials or the presence of spontaneous muscle fiber activity in the anterior tibial muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 43 publications
(78 reference statements)
6
56
0
5
Order By: Relevance
“…Just as Alzheimer disease, osteoarthritis, and presbycusis were once considered inevitable consequences of aging, "idiopathic" peripheral neuropathy has been neglected as a potentially preventable and/or treatable condition. Vrancken et al 8 have demonstrated that age at onset of chronic idiopathic axonal polyneuropathy makes little difference in the neurological and electrophysiological findings, although patients with early onset and more rapid progression are more likely to become disabled, characteristics reminiscent of Alzheimer disease.…”
mentioning
confidence: 99%
“…Just as Alzheimer disease, osteoarthritis, and presbycusis were once considered inevitable consequences of aging, "idiopathic" peripheral neuropathy has been neglected as a potentially preventable and/or treatable condition. Vrancken et al 8 have demonstrated that age at onset of chronic idiopathic axonal polyneuropathy makes little difference in the neurological and electrophysiological findings, although patients with early onset and more rapid progression are more likely to become disabled, characteristics reminiscent of Alzheimer disease.…”
mentioning
confidence: 99%
“…A large number of early studies reported that the spontaneous discharges were caused by the various denervations [101][102][103][104][105][106][107][108][109][110][111]. These spontaneous discharges that manifested fibrillation potentials were also termed "denervation potentials" in some reports.…”
Section: Denervation Supersensitivitymentioning
confidence: 99%
“…These spontaneous discharges that manifested fibrillation potentials were also termed "denervation potentials" in some reports. The spontaneous and rhythmical repetitive discharges were originated in skeletal muscles due to the denervation process [101][102][103][104][105], and the spontaneous firing activity of muscle fiber that manifested fibrillation potentials was regarded as the safe criteria for the clinical diagnosis of denervation. The spontaneous depolarizing excitations of striatal neurons were observed after the denervation caused by 6-hydroxydopamine-induced lesions of the nigrostriatal dopaminergic system [106][107][108][109][110][111].…”
Section: Denervation Supersensitivitymentioning
confidence: 99%
“…It is generally accepted to coin the disorder chronic idiopathic axonal polyneuropathy (Notermans et al, 1993;Wolfe et al, 1999;Vrancken et al, 2002;Hughes et al, 2004). The disease shows a male pre-dominance and seems to be a common hospital-referred polyneuropathy (McLeod et al, 1984;Wolfe et al, 1999;Vrancken et al, 2002;Teunissen et al, 2000;Mygland and Monstad, 2001;Rudolph and Farbu, 2007). Re-evaluation is often not recommended as no cause of the polyneuropathy is found after repeated follow-up investigation (Notermans *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, quality of life may be reduced at long-term follow-up (Notermans et al, 1994;Wolfe et al, 1999;Vrancken et al, 2002). It has been shown that physical, mental, emotional and social wellbeing seem to be impaired up to one decade after onset (Hughes et al, 2004;Teunissen et al, 2000;Erdmann et al, 2007;Rudolph et al, 2009).…”
Section: Introductionmentioning
confidence: 99%